Gestão de bibliotecas na educação superior: uma análise sobre acessibilidade na Universidade Federal da Paraíba - Silva Junior, Carlos Augusto Rolim da (2021)
Data from the World Health Organization (WHO) and the Brazilian Institute of Geography and Statistics (IBGE) show how numerous the population of people with disabilities is, both globally and nationally. The community of people with disabilities has a series of assured rights, but it is necessary that they leave the texts of the laws and become concrete, effective, so that they produce the effects and the necessary changes. Some of these changes need to happen in public library buildings and services, considering the role they play in the process of democratization of information and knowledge, which must be within the reach of everyone. In this sense, the research aimed at analyzing the adequacy of on-site and digital services of the Central Library and Sector Libraries of the Center of Applied Social Sciences (CCSA) and Center of Exact and Natural Sciences (CCEN) of the Federal University of Paraíba (UFPB) for the promotion of accessibility to people with disabilities. This was an applied research, whose approach to the problem was qualitative in nature and, as to the objectives, it had an exploratory and descriptive character. As for the technical procedures, it adopted the bibliographic and documental research, as well as, it used the direct observation technique and, for the data analysis, it followed the content analysis method. In the presentation of the results, in a first moment, the guiding documents of accessibility in the evaluation processes of the HEIs within the context of SINAES were analyzed and, after that, the production of the UFPB regarding its accessibility policy was verified. In the second moment, the data collected from the libraries studied are presented and analyzed in relation to the items of architectural and communicational accessibility. For a better understanding of the research, the theoretical foundation worked on the accessibility issues in the context of the evaluation processes of higher education. The university library and its relationship with accessibility were studied, with a view to promoting democratization and access to information and knowledge for all. From the data collected it was concluded that, in general, the three libraries in the study do not meet all the recommendations of accessibility, both architectural and communicational, requiring adjustments and improvements in important issues, which today represent barriers to their users with special needs.